Spectroscopy and Formation of Carbon Nitride by Pulse Laser Ablation in Liquid of Graphite Target - Mayyadah H. Mohsin; Khawla S. khashan (Engineering and Technology Journal, 2016)
In this work carbon nitride was synthesized by pulsed laser ablation of graphite in ammonium solution. Fourier Transform Infrared Spectroscopy (FTIR), UV-Visible Spectrophotometer and Transmission Electron Microscopy (TEM) were used to study the bonding, absorption, size and morphology of the carbon nitride nanoparticles. The FTIR absorption peak at 2121.6, 1631.7, 1384 cm-1 stretching vibration bond, it is inferred that the C ≡ N, C = N and C-N, respectively. Bonds suggested the formation carbon nitride nanoparticles. UV absorption peaks coincide with the electronic transitions corresponding to formation carbon nitride C3N4 and monocyanopolyynes. The TEM image showed the aggregation of the carbon nitride nanoparticles with size ranges from (4 to 83.3 nm); the Leaf- like structure is shown in the structure of carbon nitride suspension.